Effective Teaching Mathematics at School Level: A Perspective from Nepal - Pathak, Susmita (DMC Journal, 2023)
Mathematical facilitators all across the globe are using fresh approaches and making use of productive results, implementation of research-based methods to teach mathematics in the classroom. A cooperative knowledge-building approach, i.e. Iterative Best Evidence Synthesis Program, is required for classroom instruction. This study gives guidelines for effective educational techniques that promote instructors for varied learners by drawing on results from mathematics, the intuitive notions that have been utilized in the classroom, and recent research investigations. In examining the links between pedagogical practices and a range of social and academic student outcomes, this article draws on the histories, cultures, language, and practices for the Nepali context.